2017
DOI: 10.1039/c7cp01725a
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting bubble size in ionic liquids

Abstract: This study reports on understanding the formation of bubbles in ionic liquids (ILs), with a view to utilising ILs more efficiently in gas capture processes. In particular, the impact of the IL structure on the bubble sizes obtained has been determined in order to obtain design principles for the ionic liquids utilised. 11 ILs were used in this study with a range of physico-chemical properties in order to determine parametrically the impact on bubble size due to the liquid properties and chemical moieties prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…This IL-dependent emission zone may be due to the size of the cation; the relatively large P 44412 cation cannot penetrate into the neat F8T2 films efficiently, while the small BMP cation can penetrate and thus the n-doped region is formed. The sizes of these cations have not been reported so far, but it was reported that the free volume of BMP-TFSA is 35.36 cm 3 =mol, which is approximately four times smaller than that of tetradecyltrihexylphosphonium bis(trifluoromethylsulfonyl)amide (P 66614 -TFSA) (140.25 cm 3 =mol), 19) the cation size of which is slightly larger than that of P 44412 -TFSA. Although more careful and systematic studies are required to understand what determines the position of the emission zone, the results indicate the importance of electrolyte species in making the emission zone far away from the metal contact, which is important for avoiding optical absorption loss by metals.…”
Section: Resultsmentioning
confidence: 96%
“…This IL-dependent emission zone may be due to the size of the cation; the relatively large P 44412 cation cannot penetrate into the neat F8T2 films efficiently, while the small BMP cation can penetrate and thus the n-doped region is formed. The sizes of these cations have not been reported so far, but it was reported that the free volume of BMP-TFSA is 35.36 cm 3 =mol, which is approximately four times smaller than that of tetradecyltrihexylphosphonium bis(trifluoromethylsulfonyl)amide (P 66614 -TFSA) (140.25 cm 3 =mol), 19) the cation size of which is slightly larger than that of P 44412 -TFSA. Although more careful and systematic studies are required to understand what determines the position of the emission zone, the results indicate the importance of electrolyte species in making the emission zone far away from the metal contact, which is important for avoiding optical absorption loss by metals.…”
Section: Resultsmentioning
confidence: 96%
“…Surface nanobubbles have been reported in viscous media, 44 but in ionic liquids there have so far only been optical measurements proving micron sized and larger bubbles. 45 Another possibility for the large variance in the resistance versus diameter is that nanocapillaries have by themselves an ill defined geometry due to the production method, and that small variations of the tapering angle are not controllable. In order to increase any ordering effects platinum coated nanocapillaries were also used (analogously to ref.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, gas diffuses from the smaller bubbles to the larger ones, leading to dissolution and disappearance of the smaller bubbles. It is well documented that factors such as shell composition, fabrication method used, the relative chemical environment and temperature can substantially influence MB size and its temporal evolution (Mulvana et al, 2010;Sun et al, 2014;Lee et al, 2015b;Taylor et al, 2017).…”
Section: Gas Microbubbles: a Methods Of Controlled Drug Deliverymentioning
confidence: 99%